A Comparison of Tactic and Technical Approaches to Student Basketball Skills - Sucipto; Agus Gumilar; Alpi Pebria Lestari; Burhan Hambali (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The tactical and technical approach model is an approach model that is often used in physical education, especially in game sports, one of which is basketball. This study aims to determine the different effects of tactical and technical learning models on students' understanding and skills in basketball. The method and design of this study used an experimental method with pre-test and post-test design groups. The research sample is composed of high school students, with a total of 48 students. 12 students using a technical approach and 12 tactical students The instrument uses GPAI (Games Performance Instrument Analysis). The results obtained (1) test the similarity of the average of the two skills obtained. 000 for technical and 0.000 for tactical, it can be concluded that the two models have significant differences in basketball playing skills. (2) Then the two models have different average values; the playing skills score of the tactical approach model is 0.67 and the technical approach model is 0.55. The difference between the two approach models shows that the tactical approach model has a significantly greater effect than the technical approach model.